Caracterização molecular e controle de fungos da família Botryosphaeriaceae em fruteiras tropicais - Lima, Ingrid Bernardo de (2016)
The family Botryosphaeriaceae (Ascomycota, Botryosphaeriales) encompasses several ecologically diverse fungal species, which are usually isolated as endophytes or pathogens, from various woody hosts. The present work aimed to identify morphologically and by molecular techniques as well as to assess the pathogenicity of isolates of Botryosphaeriaceous fungi obtained from fruit plants grown in the Brazilian Northeastern region. After the isolation of DNA from the fungi the combined analyses of fragments sequency of transcribed spacer (ITS) of ribosomal DNA, translation elongation factor 1-α (TEF-1α) and β-tubulina (βt) were used to determine the phylogenetic relationships among the isolates which lead to identification of six fungal species of Lasiodiplodia, two of Neofusicoccum, one of Pseudofusicocuum and one of Neoscytalidium associated with die-back and cankers on the following host plants: Lasiodiplodia brasiliense (Manilkara zapota, Mangifera indica and Spondias purpurea), L. caatinguensis sp. nov (Anarcadium occidentale, S. purpurea, S. mombin and Citrus sinensis), L. euphorbicola (Annona muricata and Cocos nucifera), L. theobromae (S. purpurea, Talisia esculenta and A. occidentale), L. pontae sp. nov (S. purpurea and A. occidentale), L pseudotheobromae (S. purpurea, Tamarindus indica and A. occidentale), Neofusicoccum brasiliense (Psidium guajava), Neofusicoccum kwambonambiense (A. occidentale), Neoscytalidium hyalinum (A. occidentale and M. indica) e Pseudofusicoccum stromaticum (A. occidentale). As far as the morphology of isolates is concerned there were significant differences among them, mainly concerning the culture media and the incubation temperatures adopted. Generally, isolates presented a white mycelial growth, becoming dark after aging. As for pathogenicity all species were pathogenic to fruits of mango as well as to seedlings of A. occidentale and S. purpurea. All species of pathogenic Lasiodiplodia were the young plants of soursop. However, the aggressiveness of the isolates varied as the species and the host species Lasiodiplodia being the most aggressive. The cashew genotype BRS253 behaved as the most susceptible of all genotypes tested, followed by CCP76, BRS189 and BRS226, which did not present any significant difference among them. All the other genotype were considered as moderately resistant, especially BRS274 and Embrapa 51, upon which the fungal isolates showed no pathogenicity differences. Both fungicides tested were able to inhibit the fungal growth in vitro conditions, despite carbendazin had been a little more efficient than tebuconazole.